Designing and implementing Microsoft DevOps Solutions AS-400 exam guide : ace the certification exam and successfully apply Azure DevOps strategies with practical labs /: ace the certification exam and successfully apply Azure DevOps strategies with practical labs. (2022) - Chatterjee, Subhajit; Been, Henry; Deshpande, Swapneel; Gaag, Maik van der
No abstract available